Penggunaan Media Youtube untuk Mendukung Wawasan Kebangsaan di Perguruan Tinggi - Wahyuni Putri; Farida Azarah; Dewi Fitriyana; Hanifatur Rahmi; Rafi Fikri Rizani, Helfira Citra (CV. ITTC INDONESIA, 2024)
The use of YouTube media has become a primary concern in higher education as a means to enhance students' national insight. This research aims to explore the impact of YouTube use in the context of building national insight in higher education. A qualitative research method was employed through in-depth interviews with lecturers and students, as well as observation of relevant YouTube content. The results show that consistent YouTube use can broaden students' perspectives on national issues, facilitate discussions, and enhance understanding of national values. However, challenges such as the validity of information sources and content quality remain a concern. Therefore, collaborative efforts among universities, lecturers, and students are needed to optimize the use of YouTube media as a tool for enhancing national insight in the context of higher education.